PMO-225 Use of infliximab for acute severe ulcerative colitis in a district general hospital. (28th May 2012) - Alisa, A; Musa, S; Zar, S; Mahmood, A
Abstract : Introduction: The prevalence of Ulcerative colitis (UC) in the UK is 243/100 000 and carries a high lifetime risk of surgery (20%–30%). Acute severe UC (ASUC) is potentially a life threatening condition. Traditionally urgent medical treatment includes intravenous steroids followed by IV Ciclosporin in non-responders. In 2010, NICE recommended the use of Infliximab in ASUC in patients in whom ciclosporin is contraindicated or clinically inappropriate. Randomised control trials suggest colectomy is required in 30% of Infliximab recipients at 3 months and 50% at 3 years. 1 2 This retrospective study reports our experience at a busy district general hospital in South West London. Methods: The Biologic database at St. Helier's Hospital was interrogated to identify all cases of ASUC that gained funding for. Infliximab data collection was from January 2009 to June 2011. All patients had a UC disease activity index score (UCDAI)>10. Disease site was classified by the Montreal classification. Follow-up ranged from 6 to 36 months post treatment. Results: 20 patients had funding approved. 17/20 (85%) patients received Infliximab, 3/20 (15%) clinically settled pre-administration. There were 9 (53%) males and 8 (47%) females, median age 47 (range 19–57). 9 (53%) patients had left sided disease and 8/17 (47%) had extensive colitis. Median UCDAI was 11 (range 10–13). The median disease duration 4 years (range 0–15 years). During the acute presentation (pre-Infliximab), 11/17 (65%) patients received steroids, 11/17 (65%) were already on azathioprine, 15/17 (88%) 5-ASA, 3/17 (18%) 6-MP and 1/17 (6%) Tacrolimus. Following steroid therapy 4/17 (24%) had received Ciclosporin. Urgent colectomy was required in 2/17 (12%) patients. A further 6/17 (35%) underwent elective colectomy post induction, median 5 months (range 2–12 months). Complications were experienced in 3/17 (18%) and included 1 lichen planus, 1 Raynauds, 1 arthralgia. There was no mortality reported. Conclusion: Following Infliximab therapy urgent colectomy was avoided in the majority (82%) of patients. Our elective colectomy rate was not to dissimilar to those reported by main randomised control trials. Infliximab was well tolerated and provided rescue therapy prior to latent elective surgery. Competing interests: None declared. References: 1. Jarnerot G, et al. Gastroenterology 2005;128 :1805–11. 2. Gustavsson A, et al. Aliment Pharmacol Ther 2010;32 :984–9.